Health and School Performance: A n Explorato ry Quantitative Study of S chool Children in Huay Huay , Peru - Fergusson, Lee (2021)
A paucity of data in school children generally, and in non-Western schools specifically, related to health, school performance, and practice of meditation necessitated this study. The fact that almost no prior research of this type has been conducted in Latin America makes the present investigation especially worthwhile. This mostly quantitative study was carried out with 91 randomly selected school children, ranging in age from 11 to 16 years, in a remote Peruvian town in the central Andean mountains called Huay-Huay. Using a 47-question, paper-and-pencil instrument to ask students about their experience with meditation in four categories (i.e., physical health, cognitive health, emotional health, and school performance), this observational study considered whether or not the practice of meditation had a self-reported impact on student personal health and academic life, and if so to what extent. Data indicate that a majority of children in Huay-Huay reported benefits across all measures, and these were apparently stronger when students practiced meditation more regularly. Qualitative reports support these conclusions. Gender and grade level did not appear to influence this outcome.